Identifikasi Sifat-Sifat Kualitatif Warna Bulu, Bentuk Tanduk, dan Bentuk Ekor pada Domba Priangan Betina di SP3TDK Tambak Mekar Kabupaten Subang - Nabil Humam Ghifari; An An Nurmeidiansyah; Diky Ramdani (Jurnal Produksi Ternak Terapan, 2021)
Qualitative trait is one of indicators of selection that can be used as a phenotypic character of a breed. There are many traits that are usually observed to include hair color, horn shape, and tail shape. The research about “Identification of Qualitative Traits of Hair Color, Horn Shape, and Tail Shape of Priangan Ewes in SP3TDK Tambak Mekar Subang Regency” was conducted to determine the qualitive traits of Priangan Ewes in SP3TDK Tambak Mekar Subang Regency. The research conducted for ten days from January 6st 2020 to January 17st 2020. The method used in this research was survey and data collections were conducted by census method to look at the parameters of hair color, horn shape, and tail shape of Priangan Ewe in SP3TDK Tambak Mekar Subang Regency. The results showed that Priangan Ewes in SP3TDK Tambak Mekar Subang Regency were dominated by white hair color (81,82%), combination hair color (13,64%), black hair color (4,54%), and brown Priangan Ewe was not found (0%). The horn shapes of Priangan Ewe in SP3TDK Tambak Mekar Subang Regency were dominated by unhorn (68,18%), muser (27,27%), and small horn (4,54%). The tail shapes of Priangan Ewe in SP3TDK Tambak Mekar Subang Regency were dominated by tail shape ngabuntut beurit (86,36%) and ngabuntut bagong (13,64%). In conclusion, SP3TDK Tambak Mekar Subang Regency has Priangan Ewes with the majority qualitative traits of white hair color, unhorn, and ngabuntut beurit.